Pengaruh Penggunaan Media Sosial Instagram Dinas Komunikasi Dan Informatika Kota Samarinda Terhadap Partisipasi Publik Untuk Mendukung Prinsip E-Government: The Influence Of Instagram Social Media Usage By The Communication And Information Agency Of Samarinda City On Public Participation In Supporting The Principles Of E-Government - Ananda Putra, Alfin; Muhammad Habibi; Deandlles Christover; Ahmad Yani (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2025)
The background of this research was from the acknowledgement of the importance of social media as a form of an interactive communication tool between the government and the public, which is expected to improve the public engagement in electronic governance. The root of problems this research addresses are whether the usage of Instagram as social media by the Samarinda City Communication and information Office influences the public participation and whether the formulated hypothesis are true or not. The study also aims to determine the impact of the usage of Instagram as a social media towards public participation in supporting e-government principles and to test the validity of the research hypothesis. The research evaluates social media using the 4C indicators by Chris Heuer, which are Context, Communication, Collaboration, and Connection. While Public Participation is assessed by using the indicators from International Association for Public Participation (IAP20, such as Inform, Consult, Involve, Collaborate, and Empower. Based on the result of the data analysis, it was found that the usage of Instagram as a social media by the Samarinda City Communication and Information Office has a very strong/high impact towards public participation regarding to support the e-government principles. This result was proven by statistical testing using the Spearman's Rank Correlation Coefficient formula which was conducted using the SPSS version 30, yielding a result of 0,884 (rounded to 0.90). Thus, the hypothesis proposed has been proven, and the alternative hypothesis (Ha) is accepted by the data, while the null hypothesis (H0) is rejected.